The Role of Empowerment Mechanisms in Reducing Job Burnout By Applying to the Saudi Standards, Metrology and Quality Organization - HOUARI, Moaredj; Alqrni, Ahmed (The Arab Journal of Administration, 2023)
The study addressed the role of enabling mechanisms in reducing functional combustion by applying to the Saudi Authority for Specifications، Standards and Quality and sought to achieve a set of objectives consisting of monitoring trends that relate to the phenomenon of functional combustion and the impact of the empowerment process and its mechanisms، and clarifying the link of the empowerment process to the phenomenon of functional combustion in the Saudi Authority for Specifications، Standards and Quality. The statistical processing program was used to analyze data to measure the main variables in the study. The study concluded a number of recommendations، most notably the development and strengthening of the Authority’s decision-making and participation policy through task forces، committees، departments and other units، which has a positive impact on the roles of presidents and subordinates alike، supports the atmosphere of trust and mutual cooperation، stimulates the creative abilities of employees and works to develop comprehensive strategies، based on optimal practices in distinguished organizations، by providing the right climate that stimulates and provokes the behaviors of workers، and supports teams of work. Collectively، take care of the interest of the workers and inform them that the authority belongs to them، which reflects positively on their actions.